Theorizing China’s rise in and beyond international relations - Pan, Chengxin; Kavalski, Emilian (Oxford University Press, 2018)
China's rise, like the demise of the Soviet Union, is one of the defining events in the contemporary world. Yet, while the unexpected Soviet collapse and the end of the Cold War sparked the ‘Third Debate’ in International Relations (IR) theory, it is puzzling that the rise of China has yet to generate a comparable process of shell-shock and soul-searching among IR theorists. Just as the end of the Cold War is more than simply the end of a bipolar power struggle per se, so too China's rise is much more than the familiar ascendancy of another great power. Rather, it is also a complex, evolving and possibly border-traversing and paradigm-shattering phenomenon in global life that, on the one hand, requires fresh and innovative theorizing in and beyond IR and, on the other hand, potentially offers new insights for us to rethink world politics more broadly. This article introduces this Special Issue that seeks to tentatively respond to this theoretical, epistemological and ontological challenge. It draws attention to the blind spot in IR theorizing on China, and calls for deeper engagement between IR theory and China's rise that goes beyond mere ‘theory-testing’ within the existing perimeters of mainstream IR.